The Victorian Literature Analysis of Ambition and Self-Improvement using Maslow's Theories on Dickens Message in Great Expectations - Arif Cahyono (International Journal of English and Applied Linguistics (IJEAL), 2022)
This research discusses the victorian literature analysis of ambition and self-improvement using Maslow's theories on Dickens's message in Great Expectations and the purpose of analyzing ambition and self-improvement in Dickens's Message Novel Great Expectations. The researcher used the analysis of industry and self-improvement in Dickens's Message in Great Expectations theory of Maslow. This research analyzes ambition and self-improvement in Dickens's Message in Great Expectations that occurred in Great Expectations. Analysis using  descriptive qualitative methods to identify, explain, and explore the data found in the novel. The researcher used a coding sheet as the instrument to find out the valid data. This research is conducted to answer the problems concerning the victorian literature analysis of ambition and self-improvement using Maslow's theories on Dickens's message in Great Expectations in the novel. The research, the victorian literature analysis of purpose and self-improvement using Maslow's ideas on Dickens message in Great Expectations concerning Maslow's theories moreover partitions human identity into three major components: Brain research is changed in its approach to diverse human characteristics, and like each other trait that characterizes people, aspiration can be clarified with various mental theories. On the one hand, ambition and self-improvement may be closely related to inspiration, mainly accomplishment inspiration, and may be characterized by Maslow's hypothesis of human motivation. The author found that there was ambition and self-improvement behaviour in pip where pip was the self of Charles Dickens.